Technologies of the self in the writings of William S Burroughs - Williams, Michael John (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1996)
William Burroughs's profane life has been an affront to conventional morality, and his transgressive works have strained against the thematic and formal boundaries of literature. Although he has remained a problematic figure, he is gradually gaining recognition as a literary innovator. This thesis argues that his writings may be understood as technologies of the self, that is, the texts are tools that the writer Oses to transform himself. The Introduction outlines the problems that his writings pose for criticism; provides an overview of critical responses to his work; and demonstrates the appropriateness of Michel Foucault's theory of the technologies of the self as an approach to his texts. Furthermore, it makes a comparison between Burroughs's concerns and similar concerns evident in Foucault. The most prominent of these is a fear of control, and a desire to escape from control. It is argued that this similarity arises from the writers' shared experience of homosexuality in the twentieth century. This experience provokes them to undertake aÂ·work of homographesis, in which they attempt to undermine the construction of identity in text, whilst simultaneously reinscribing identity in problematized autobiographical writing. Chapter One provides a corrective to the critical neglect of Burroughs's homosexuality and focuses on his sexual problematic as a key factor in the development of his literary style. It argues that the writer has an abject imagination that was precipitated by three principal traumatic experiences: his homosexuality, his addiction to opiates, and the accidental shooting of his wife. The chapter examines the way that the writer develops his unique literary style, the routine, in an attempt to express his psychic disintegration. The routine becomes the basic building block of Naked Lunch, serving both as a cathartic release of psychic anguish and as an attempt to subvert repressive social and linguistic structures. The metaphor of the anal aesthetic is introduced to describe the intersection of linguistic, psychic and political strategies in the texts. Chapter Two addresses the period,subsequent to Naked Lunch, in which Burroughs experimented extensively with the cut-up technique to develop a form of aleatory collage. The chapter argues that the writer hoped that the technique would enable him to transform himself and to~discover a new way of thinking, but suggests that its extreme nature both isolated him from his audience and intensified his psychic abjection. Chapter Three follows on from this to argue that the writer responds to the limitations of the cut-up in The Wild Boys by returning to a more intelligible form of writing. This return corresponds with an attempt to inscribe homosexual themes into his work directly. However, the combination of a homosexual agenda and the writer's defence against the identity loss of abjection leads him to assert a radical masculine identity that causes him to perceive women as the chief perpetrators of control. As a result, he rejects women from his mythological system. Chapter Four suggests that in Cities of the Red Night and The Place of Dead Roads the writer moves away from the radical queer agenda of The Wild Boys in the hope of discovering a form of ethics that avoids the traps of universalized humanism and the harsh "othering" of the queer agenda. The chapter draws a parallel between Burroughs's individualized ethics and Foucault's idea of an ethics grounded in aesthetic self-fashioning. Chapter Five examines The Western Lands, in which the writer confronts death in order to discover the nature of individual value in a normalized culture. Like Foucault, Burroughs believes that the most important task in a limited existence is the dandyistic creation of the self.
Keywords: Burroughs, William S., 1914- -- Criticism and interpretation